2019
DOI: 10.1186/s12872-019-01275-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the DPP-4-GLP-1 pathway improves exercise tolerance in heart failure patients: a systematic review and meta-analysis

Abstract: BackgroundThe most significant manifestation of heart failure is exercise intolerance. This systematic review and meta-analysis was performed to investigate whether dipeptidyl peptidase-4 (DPP-4) inhibitors or glucagon-like peptide 1 receptor agonists (GLP-1 RAs), widely used anti-diabetic drugs, could improve exercise tolerance in heart failure patients with or without type 2 diabetes mellitus.MethodsAn electronic search of PubMed, EMBASE and the Cochrane Library was carried out through March 8th, 2019, for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have reported that some antidiabetes drugs may have beneficial effects in HF, including dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide-1 receptor agonists (GLP-1 RAs), and SGLT-2 inhibitors. Our previous meta-analysis demonstrated that DPP-4 inhibitor and GLP-1 Ras may help improve exercise capacity in HF patients with or without diabetes (29), but these trials showed no improvement in LVEF (30)(31)(32), except in a trial with a small sample size (33). SGLT-2 inhibitors may be the most promising choice among these three kinds of drugs detailed above, according to recent meta-analyses (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that some antidiabetes drugs may have beneficial effects in HF, including dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide-1 receptor agonists (GLP-1 RAs), and SGLT-2 inhibitors. Our previous meta-analysis demonstrated that DPP-4 inhibitor and GLP-1 Ras may help improve exercise capacity in HF patients with or without diabetes (29), but these trials showed no improvement in LVEF (30)(31)(32), except in a trial with a small sample size (33). SGLT-2 inhibitors may be the most promising choice among these three kinds of drugs detailed above, according to recent meta-analyses (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…to better exercise tolerance. 28 The implications of these mechanisms for physical function, however, again remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Dipeptidyl peptidase‐4 inhibitors (DPP4i) act via the same incretin pathway as GLP‐1RAs to improve glycaemic control 26 . Although these have failed to demonstrate the same level of cardiometabolic and weight‐lowering benefits as GLP‐1RA, there is evidence that these agents might improve oxygen consumption by the muscles and mitochondrial biogenesis through the GLP‐1 signalling pathway, 27 translating to better exercise tolerance 28 . The implications of these mechanisms for physical function, however, again remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 20% to 46% of people have a lifetime risk of HF, and the incidence is increasing. 1 3 Many cardiac diseases eventually lead to HF. 4 Because the heart has compensatory mechanisms, patients undergo the cardiac remodeling process, which leads to changes in the ionic channel, pump, exchanger densities, and kinetics, and this results in inevitable HF.…”
Section: Introductionmentioning
confidence: 99%